2016
DOI: 10.4103/1658-354x.169473
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of ropivacaine with and without dexmedetomidine in axillary brachial plexus block: A prospective randomized double-blinded clinical trial

Abstract: Background:Addition of dexmedetomidine to ropivacaine for peripheral nerve blocks has shown to improve the efficacy of ropivacaine by prolonging the duration of analgesia. This study was undertaken to evaluate the effects of ropivacaine alone and in combination with dexmedetomidine in the axillary block.Materials and Methods:A total of 80 patients belonging to American Society of Anesthesiologists physical status I, II, and III, scheduled for elective forearm and/or hand surgeries were randomly allocated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 8 publications
6
14
0
1
Order By: Relevance
“…Only 6 studies reported the duration of analgesia and had complete data to pooling. [ 12 , 14 , 17 , 19 , 20 , 22 ] The result indicated that dexmedetomidine as an adjuvant prolonged the duration of analgesia significantly by an average of 303.04 minutes compared with the control group (MD, 303.04 minutes; 95% CI 228.84–377.24 minutes, I 2 = 86%; P < .00001) (Fig. 7 ).…”
Section: Resultsmentioning
confidence: 96%
“…Only 6 studies reported the duration of analgesia and had complete data to pooling. [ 12 , 14 , 17 , 19 , 20 , 22 ] The result indicated that dexmedetomidine as an adjuvant prolonged the duration of analgesia significantly by an average of 303.04 minutes compared with the control group (MD, 303.04 minutes; 95% CI 228.84–377.24 minutes, I 2 = 86%; P < .00001) (Fig. 7 ).…”
Section: Resultsmentioning
confidence: 96%
“…There were 515 patients in the DEX group and 499 patients in the control group among all 18 studies. [ 16 , 22 38 ] The definition of duration of sensory block varied from time interval between LA administration or complete sensory block to complete sensory recovery. Pooled analysis showed significantly prolonged sensory block duration when combined with DEX (WMD 257 minutes, 95%CI 191.79–322.24, P < 0.001), compared with that without DEX, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There were 498 patients in the DEX group and 482 patients in the control group among 17 studies, [ 16 , 22 35 , 37 , 38 ] whereas 1 study was excluded without detailing motor block. The definition of duration of motor block varied, mostly defined as the time interval between LA administration to complete motor sensory recovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…En primer lugar, destacar que todos los artículos analizados corresponden a ECR que compararon resultados de bloqueos de nervio periférico con y sin uso de DEX perineural en diferentes abordajes de plexo braquial. En líneas generales, los trabajos analizados son bastante heterogéneos entre sí cuanto a contexto quirúrgico y metodología anestésica, aun así, la mayoría presentan un nivel moderado-alto en cuanto a calidad de evidencia (según escala GRADE) así como nivel moderado-bajo de sesgo (según escala COCHRANE) (18,20,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Dado que la mayoría de los ensayos clínicos implicaron el uso de anestesia general e instalación de catéter para bloqueo continuo de nervio periférico, no se pudo estudiar adecuadamente los tiempos de latencia y, por ello, no se evaluó este punto en este subgrupo.…”
Section: Dexmedetomidina Y Bloqueos De Extremidad Superiorunclassified